Influence of organizational culture and communication on the successful implementation of information technology in hospitals - Xie, S.; Helfert, M.; Lugmayr, Artur; Heimgärtner, R.; Holzinger, A. (2013)
In this paper, we report on a case study examining types of organizational culture influencing communication as an important factor in the study of successful IT adoption and implementation in health care. We observed a hospital organization and focused on technological innovations and the accompanying communication factors in the successful implementation of IT. The results demonstrate the importance of the organizational culture as an important factor in establishing well-balanced communication as a primary influence factor in the implementation of new technologies. Based on theoretical and empirical insights, we propose a model describing the relationship of organizational culture, communication, and the level of success in the implementation and adaptation of new IT systems in hospitals. © 2013 Springer-Verlag Berlin Heidelberg.